Using insect repellents safely - Buffington, E. J., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet describes how to choose insect repellents, and discusses common repellents available to consumers, including DEET, permethrin, and botanical products.
CEPEP 8/02, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Insect baits and repellents -- Safety measures; Pesticides -- Safety measures